Clinical characteristics and prognostic factors of 60 patients with acquired immune deficiency syndrome combined with Cryptococcus neoformans - Saiduo Liu; Wei Chen; Fang Cheng; Xinchun Ye; Ning Pan; Hongzhou Lu (BMC Infectious Diseases, 2023)
Abstract Objective Cryptococcal meningitis (CM) threatens people’s health and is the main cause of opportunistic fungus-related death in acquired immune deficiency syndrome (AIDS) patients. Herein, we investigate the clinical characteristics and prognostic factors of AIDS patients with Cryptococcus neoformans in Wenzhou, Zhejiang Province, China. Methods Our study enrolled AIDS patients diagnosed with Cryptococcus neoformans infection who were hospitalised in our hospital. They were divided into Group A (32 patients with CM) and Group B (28 patients without CM) according to their diagnosis. The differences between the two groups of patients’ clinical symptoms, imaging examinations and laboratory examinations were observed. Statistical methods were used to analyse the difference in prognosis between the two groups. Results Headache and fever were the most common clinical characteristics for patients with CM, while respiratory symptoms and fever were the most common clinical characteristics for patients without CM. The positive rate of cryptococcal capsular antigen, India ink staining and culture in the cerebrospinal fluid examination was higher in the CM patients than in the non-CM patients. The overall morbidity and mortality rate after systemic antifungal therapy was higher in the CM patients than in the non-CM patients. A higher incidence of headache, impaired consciousness, nuchal rigidity, first intracranial pressure > 200 mmH2O and mortality was observed in the CM patients than in the non-CM patients. Multifactorial logistic regression analysis showed that headache risk factors affecting the patient’s prognosis at 12 weeks. Conclusion Patients with AIDS diagnosed with Cryptococcus neoformans infection have insidious clinical symptoms in the early stage, and their manifestation is often non-specific, resulting in poor prognosis and high mortality among CM patients compared to patients without CM. Therefore, early identification and timely antifungal therapy before the disease progresses to meningitis are of great value in improving the survival rate of patients.